The safety of sports in children with inherited arrhythmia substrates - Katyal, Abhay; Li, Christopher O. Y.; Franciosi, Sonia; Sanatani, Shubhayan (Frontiers in Pediatrics, 2023)
Sudden cardiac death (SCD) is a rare and devastating event in children and remains a leading cause of death in young athletes. Channelopathies and cardiomyopathies, in particular long QT syndrome (LQTS), catecholaminergic polymorphic ventricular tachycardia (CPVT), hypertrophic cardiomyopathy (HCM), and arrhythmogenic cardiomyopathy (ACM) are associated with exercise-related SCD. Implantable cardioverter-defibrillators (ICDs) are often placed for secondary prevention for athletes with cardiomyopathy or channelopathy. There remains concern regarding the safety of return to participation with an ICD in place. Guidelines have historically recommended that patients with inherited heart rhythm disorders be restricted from competitive sports participation. Increasing evidence suggests a lower risk of exercise-related cardiac events in young athletes with inherited heart rhythm disorders. In this review, we highlight current knowledge, evolving guidelines, and present a multidisciplinary approach involving shared decision-making and appropriate planning for safe sports participation of children with inherited heart rhythm disorders.